New triterpenoids from the Cyclocarya paliurus (Batalin) Iljinskaja and their anti-fibrotic activity. (December 2022) - Liu, Yao; Zhang, Xuan-Xuan; Xu, Su-Su; Fang, Si-Yang; Zhu, Li-Ping; Song, Zhe; Shang, Xu-Lan; Fang, Sheng-Zuo; Pan, Ke; Cao, Xiao-Long; Yin, Zhi-Qi
Abstract: Cyclocarya paliurus, a Chinese herbal medicine and new food resource, contains a triterpenic-acid-rich extract that demonstrated ameliorative effect on diabetic nephropathy (DN). A more in-depth discovery of functional components led to the isolation of seven new triterpenoids including two pentacyclic triterpenes, 1 α, 2 α, 3 β, 23-tetrahydroxyolean-12-en-28-oic acid and 2 α, 3 β, 22α-tirhydroxyurs-12-en-28-oic acid 28- O - β -D-glucopyranoside, and five tetracyclic triterpenoid glycosides (cypaliurusides N-R), together with twelve known compounds from the leaves of C. paliuru s. Their structures were determined using a comprehensive analysis of chemical and spectroscopic data. Partial compounds were assessed for anti-fibrotic activities in high-glucose and TGF-β1 induced HK-2 cells. Compound 16 remarkably decreased the level of fibronectin with an inhibition rate of 37.1%. Furthermore, 16 effectively alleviated the epithelial-mesenchymal transformation (EMT) process by upregulating E-cadherin expression and downregulating α-SMA expression, and it significantly decreased the level of the transcriptional inhibitors (Snail and Twist) of E-cadherin. The discovery of anti-fibrotic compounds from C. paliurus provides the potential utilization and functional candidates for the DN prevention. Graphical abstract: Seven new triterpenoids were isolated from the Cyclocarya paliurus and partial compounds could remarkedly decrease the level of fibronectin in high-glucose and TGF-βl induced HK-2 cells. Image 1 Highlights: Seven new triterpenoids were isolated from Cyclocarya paliurus. Cyclocarioside C provided the safe and functional candidates for DN. It provided the scientific evidence for anti-fibrotic activity of Cyclocarya paliurus.